Pengaruh Produk, Persepsi Harga, dan Promosi Terhadap Keunggulan Bersaing untuk Meningkatkan Kinerja Pemasaran Produk Furniture Kota Pasuruan - Aulia, Maulidiah Amirul (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2022)
Every UMKM Furniture entrepreneur is required to understand and understand what is happening in the market so that they are able to compete with other entrepreneurs and improve marketing performance. In addition, business actors must have the ability to create competitive advantage. Competitive advantage in this study can be seen from several variables including, product, price and method of promotion. The purpose of this study is to analyze internal and external factors to create a competitive strategy through products, price perceptions, and promotion of furniture products in Pasuruan. In addition, it is also to find out what factors are most influential in determining competitive strategies through products, price perceptions and promotion of furniture products in Pasuruan. The population observed in this study were furniture entrepreneurs in Pasuruan. samples taken using proportionate random sampling technique as many as 120 respondents. Data collection analysis techniques were carried out by observation, questionnaires and interviews. The findings of this study indicate that the regression coefficient value of the product variable has a significant effect on marketing performance and competitive advantage. Among the three variables consisting of product, promotion, product price, it can be seen that the product variable is the most influential in increasing marketing and competition in the furniture business in Pasuruan.